The outcome of newborn admitted in neonatal care unit, center teaching hospital of pediatric , Baghdad Al-krakh, 2015 - Ibrahim, Riyadh Mraweh; Hashem, Bushra Jabbar (AL-Kindy College Medical Journal, 2019)
Background: Neonatal period is a very vulnerable period of life due to many problems, In spite of advances in perinatal and neonatal care still, the mortality rate of neonate high especially in developing country The World Health Organization estimates that globally four million neonatal deaths per year, Developing countries account for around 99% of the neonatal mortality in the world, In Iraq. Neonatal mortality rate about 19 per 1000 live births which represent 56% of child death below 5 years age in 2012. The hospital in the study represents the larger pediatric hospital in Iraq. It contains 400 children's beds and 24 neonatal incubators.Aims of the study: are to determine the institutional new-born case fatality rate and the cause of death in the neonatal care unit.Method; The study is cross-section study of the population sample of neonatal care unit of central teaching hospital of pediatric in Baghdad Al-krakh health directorateResult: Study appear total neonate admission during 2015 was 1977 neonates mortality rate 9% Four main causes of death were Respiratory related condition, Bacterial sepsis, Disorder related to short gestational and low birth weight not relayed to elsewhere classification and congenital malformation 37.5%, 33.3%, 7.1% and 7.1% respectively while the main primary cause of morbidity were Neonatal jaundice, Respiratory related condition, Bacterial sepsis and 37.5%, 35.2%. 14.1% respectively Conclusions: The majority of morbidity and mortality can prevent by appropriate intervention